An APETALA2/ethylene responsive factor transcription factor GmCRF4a regulates plant height and auxin biosynthesis in soybean - Xu, Zhiyong; Wang, Ruikai; Kong, Keke; Begum, Naheeda; Almakas, Aisha; Liu, Jun; Li, Hongyu; Liu, Bin; Zhao, Tuanjie; Zhao, Tao (Frontiers in Plant Science, 2022)
Plant height is one of the key agronomic traits affecting soybean yield. The cytokinin response factors (CRFs), as a branch of the APETALA2/ethylene responsive factor (AP2/ERF) super gene family, have been reported to play important roles in regulating plant growth and development. However, their functions in soybean remain unknown. This study characterized a soybean CRF gene named GmCRF4a by comparing the performance of the homozygous Gmcrf4a-1 mutant, GmCRF4a overexpression (OX) and co-silencing (CS) lines. Phenotypic analysis showed that overexpression of GmCRF4a resulted in taller hypocotyls and epicotyls, more main stem nodes, and higher plant height. While down-regulation of GmCRF4a conferred shorter hypocotyls and epicotyls, as well as a reduction in plant height. The histological analysis results demonstrated that GmCRF4a promotes epicotyl elongation primarily by increasing cell length. Furthermore, GmCRF4a is required for the expression of GmYUCs genes to elevate endogenous auxin levels, which may subsequently enhance stem elongation. Taken together, these observations describe a novel regulatory mechanism in soybean, and provide the basis for elucidating the function of GmCRF4a in auxin biosynthesis pathway and plant heigh regulation in plants.